A change of mind - Chin, Leonard Khe Wu * (Sunway University College, 2010)
In between Malaysian secondary school and pre-university study, there exists a great divide. While they may possess good study habits and are eager to learn, the vast majority of students at pre-university level are ill-prepared for what is required of them at this level; for many, their sufferings continue right through university. How do we, as teachers, assist them to overcome their difficulties and get them on the right track? The answer often lies in changing the mindsets and mentalities of such students, challenging traditional and often misleading philosophies and dicta, and creating awareness of realities and issues that all university students have to accept.